2006
DOI: 10.1016/j.virol.2005.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomaviruses bind a basal extracellular matrix component secreted by keratinocytes which is distinct from a membrane-associated receptor

Abstract: Human papillomaviruses (HPVs) have previously been shown to adsorb to cultured cells via membrane-associated heparan sulfate (HS) and alpha6 integrin. We demonstrate that cultured keratinocytes uniquely secrete a component into the basal extracellular matrix (ECM) which can function to adsorb HPV particles which can then be internalized by adherent cells. This uncharacterized basal ECM adsorption receptor was secreted by normal human epidermal keratinocytes (NHEK) and by each of the four keratinocyte-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 41 publications
8
98
0
Order By: Relevance
“…In these studies, which were focused on the primary binding events rather than uptake/infection, we found that VLPs and PsV particles showed similar binding patterns to those found previously for HPV11 L1 VLPs, HPV11 PsVs and native HPV11 virions (Culp et al, 2006a). The data suggest that the four types of VLP capsid tested in this study showed qualitative differences in binding to HS, ECM and purified LN5, although direct quantification of K d values for binding to purified individual components awaits additional experimentation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In these studies, which were focused on the primary binding events rather than uptake/infection, we found that VLPs and PsV particles showed similar binding patterns to those found previously for HPV11 L1 VLPs, HPV11 PsVs and native HPV11 virions (Culp et al, 2006a). The data suggest that the four types of VLP capsid tested in this study showed qualitative differences in binding to HS, ECM and purified LN5, although direct quantification of K d values for binding to purified individual components awaits additional experimentation.…”
Section: Discussionsupporting
confidence: 81%
“…The role of HS receptors in vivo has been examined recently in a mouse vaginal infection model using PsVs of several HPV types and, interestingly, preferential initial binding of HPV PsVs to basement membrane (BM) components was demonstrated (Johnson et al, 2009;Roberts et al, 2007). In addition, preferential binding of several HPV VLPs to the BM in human cervical tissue sections was reported previously (Culp et al, 2006a). These recent studies support an important role for BM/ECM components in the initial binding and uptake of HPV capsids in vivo, as a reservoir for uptake of virions via cellular filopodia (Schelhaas et al, 2008;Smith et al, 2008), and support a role for the importance of ECM-binding events that can be observed in vitro when keratinocyte cell lines representing the natural host cell are used.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Following primary attachment and internalization, acidification of early endosomes triggers capsid disassembly (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24).…”
mentioning
confidence: 99%